Improving building efficiency using low-e coating based retrofit double glazing with solar films - Somasundaram, Sivanand (2022)
As more new green buildings are being built, the daunting task of retrofitting old building stock to make them sustainable still exists. This paper discusses primarily about retrofit double glazing, which is easily implementable for old building stock, and discusses other complementary steps to be taken to maximize the energy saving impact of the retrofit double-glazing solution. These include installation of a solar film prior to retrofit installation, with considerations for optimal natural day lighting, active scheduling of air-conditioning systems, and lighting systems as well. It was observed that combination installation of solar film with retrofit double glazing reduces the annual HVAC energy consumption by up to 20%. Active scheduling of compressor operation can further reduce HVAC energy consumption by about 7%. Finally, active lighting control which autonomously adapts according to available daylight can increase the total savings further by up to 17%. In summary, simple, cost effective retrofit solutions leading to an existing building's annual electricity reduction of 30–40% is demonstrated.